The consolidation of the Madeira Wine Industry : mergers & acquisitions - Fontes, Francisco Borges Gonçalves (2017)
The Madeira Wine industry is comprised by 6 companies, competing in the export market of Fortified Wines with bigger players like producers of Port, Sherry or Marsala. In this paper, I explore the possibility of a consolidation of the Madeira Wine companies, for a purpose of maximizing the economies of scale available in the industry. Synergies from this merger can amount to nearly 40% of the total value of the companies together. For a complete overview of this operation, an analysis and valuation of the companies is presented beforehand and, afterwards, details of the suggested deal surrounding this industry consolidation.